MO484ADVERSE OUTCOMES ASSOCIATED WITH ORAL ANTITHROMBOTIC USE IN PATIENTS WITH MODERATE-TO-ADVANCED CHRONIC KIDNEY DISEASE*. (29th May 2021) - Laville, Solene; Lambert, Oriane; Hamroun, Aghiles; Metzger, Marie; Jacquelinet, Christian; Laville, Maurice; Frimat, Luc; Fouque, Denis; Combe, Christian; Ayav, Carole; Pecoits-Filho, Roberto; Stengel, Benedicte; et al.
Abstract: Background and Aims: The use of oral antithrombotics in patients with chronic kidney disease (CKD) is challenging because of altered pharmacodynamics/pharmacokinetics. Patients prescribed oral anticoagulant are at high risk of bleeding, and possibly also acute kidney injury (AKI) and progression to kidney failure. We assessed bleeding, AKI, and kidney failure risks associated with oral anticoagulant and/or antiplatelet agent prescription in patients with moderate-to-advanced CKD. Method: CKD-REIN is a prospective cohort of 3022 nephrology outpatients with CKD stages 2-5 at inclusion. Drug prescriptions and their duration were collected prospectively. We used cause-specific Cox proportional hazard models to estimate hazard ratios (HR) for bleeding (identified through hospitalizations), AKI (as defined according to KDIGO 2012), and kidney failure. Prescriptions of oral antithrombotics were treated as a time dependent variable and models were adjusted for baseline comorbidities, laboratory data, and other medications. Results: At baseline, 339 (11%) patients (65% men; median age 69 [interquartile range (IQR), 60-76] years; median eGFR 32 [IQR, 23-41] were prescribed oral anticoagulants only, 1095 (36%) antiplatelet only, and 101 (3%) both anticoagulant and antiplatelet. Over a median follow-up of 3 years (IQR, 2.8-3.1), 152 patients experienced a bleeding event requiring hospital visit/stay (crude incidence rate (IR): 1.9% person-years [95%CI, 1.6-2.2]), 414 patients experienced AKI (crude IR: 5.4 % person-years [4.9-5.9]), and 270 experienced kidney failure (crude IR: 3.4 % person-years [3.0-3.8]). A significant interaction was found between oral antithrombotics and eGFR (interaction p=0.03). The adjusted HRs [95%CI] for bleeding associated with prescriptions of antiplatelets only, oral anticoagulants only, and antiplatelet + oral anticoagulant were respectively 0.58 [0.30; 1.11], 2.62 [1.39; 4.93], and 5.76 [2.85; 11.66] in patients with a baseline eGFR < 30 mL/min/1.73m 2 . In patients with baseline eGFR ≥ 30 mL/min/1.73m 2, the adjusted HRs [95%CI] for bleeding associated with prescriptions of antiplatelets only, oral anticoagulants .......only, and antiplatelet + oral anticoagulant were respectively 0.98 [0.48; 1.98], 1.91 [0.87; 4.20], and 1.54 [0.46; 5.12] (Figure 1A ). An increased risk of AKI risk was associated with the prescription of oral anticoagulants (adjusted HR [95%CI]: 1.91[1.48; 2.46]) but not the prescription of antiplatelets (1.24[0.98; 1.56], Figure 1B ). No significant interactions were found between oral anticoagulants and eGFR or antiplatelet agents. Kidney failure was not associated with the prescription of oral antithrombotics of any type (Figure 1C ). No significant interactions were found with eGFR and antiplatelet agents. Conclusion: This study confirms the risk of AKI in CKD patients prescribed oral anticoagulants. It also highlights the potential aggravating effect of combining anticoagulants and antiplatelet on the risk of bleeding in this population.